RESEARCH ON HOW TO INVESTIGATE TO DEVELOPE THE AETHETIC CULTURE OF ASPIRING FOREIGN LANGUAGE TEACHERS INVESTIGATIVE EFFORT ON DEVELOPING THE AETHETIC CULTURE OF ASPIRING FOREIGN LANGUAGE TEACHERS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This investigative effort explores the importance and methods of developing the aesthetic culture of aspiring foreign language instructors. It delves into how language proficiency, cultural sensitivity, creative pedagogy, and continuous professional development contribute to enriching teaching practices. The article emphasizes the integration of arts and humanities into language education to foster deeper cultural understanding and enhance student engagement.